PENGARUH KARAKTERISTIK TUJUAN ANGGARAN TERHADAP TINGKAT PENYERAPAN ANGGARAN DENGAN PENGAWASAN INTERNAL SEBAGAI VARIABEL MODERATING - Yustini, Santi (Esensi: Jurnal Bisnis dan Manajemen, 2014)
This study examines the effect of budgetary goal characteristics to budget realization rate with internal control as a moderating variable. Respondents in this study are head of division in the Islamic State University Syarif Hidayatullah Jakarta. Convenience sampling method used in this research, while multiple regression and moderate regression analysis used to data analizing. The results show that budgetary participation, budgetary evaluation, budgetary feedback, budget goal clarity and budget goal difficulty  simultaneously and significantly influence budget realization rate, and the result of analysis partially on an independent variable is not influencing to budget realization rate. And Internal control can’t be a moderating variable for budgetary participation.DOI: 10.15408/ess.v4i1.1959